The Sage encyclopedia of educational research, measurement, and evaluation - Frey, Bruce B. (SAGE Reference, 2018)
"In an era of curricular changes, experiments, and high-stakes testing, educational measurement and evaluation are more important than ever. In addition to expected entries covering the basics of traditional theories and methods, The SAGE Encyclopedia of Educational Research, Measurement, and Evaluation also covers important sociopolitical issues and trends influencing the future of that research and practice. Textbooks, handbooks, monographs, and other publications focus on various aspects of educational research, measurement, and evaluation, but to date, there exists no major reference guide for students new to the field. This comprehensive work fills that gap, covering traditional areas while pointing the way to future developments"--Provided by publisher.